Battery
By introducing porous ceramic layer and inorganic particles into the separator of the lithium-ion secondary battery, and combining with the electrolyte of organic solvents, the contradiction between the rate performance and safety performance of the lithium-ion secondary battery is solved, and high fast charging cycle is achieved Take into account both performance and safety performance.
Patent Information
- Application Number
- CN202411607384.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-12
- Publication Date
- 2024-12-13
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
In the process of improving the rate performance and fast charging cycle performance of existing lithium-ion secondary batteries, the needle-punching strength performance of the diaphragm decreases, affecting the safety performance of the battery.
The porous structure of the ceramic layer is used as the separator and contains inorganic particles. By controlling the number and coverage of the surface diameter of the ceramic layer ≥0.5μm, the porosity and puncture strength of the separator are improved, and the electrolyte of organic solvents is combined to improve the ion conduction performance and Battery safety performance.
Without affecting the battery safety performance, the fast charging cycle performance and rate performance of lithium-ion secondary batteries are improved, while the heat resistance and stability of the diaphragm are enhanced, avoiding the fast charging cycle performance of the battery by coating the glue layer. Adverse effects.
Smart Images

Figure CN119133778A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of batteries, and in particular to a battery. Background Art
[0002] With the popularization of 3C products and the rise of the electric vehicle market, the demand for lithium-ion secondary batteries is increasing. As a key component of lithium-ion secondary batteries, the separator directly affects the safety, rate, fast charging cycle and other performance of lithium-ion secondary batteries.
[0003] In order to improve the rate performance and fast charge cycle performance of lithium-ion secondary batteries, the traditional solution is mainly to improve the ion conductivity of the separator by increasing the porosity of the substrate, thereby improving the fast charge cycle performance and rate performance of the battery. However, as the porosity of the substrate increases, the needle puncture strength of the separator will decrease, thus affecting the safety performance of the battery. Summary of the invention
[0004] In order to solve the above technical problems existing in the prior art, the present invention provides a battery. The separator in the battery of the present invention has the properties of large porosity and high puncture strength, so that the battery can have high fast charge cycle performance and rate performance without affecting safety performance.
[0005] The present invention provides a battery, the battery comprising a positive electrode sheet, a negative electrode sheet, an electrolyte and a separator located between the positive electrode sheet and the negative electrode sheet, the separator comprising a substrate and a ceramic layer located on one side or both sides of the substrate, the ceramic layer comprising inorganic particles, the ceramic layer being a porous structure, the porous structure comprising pores with a diameter of ≥0.5 μm, the number of pores with a diameter of ≥0.5 μm within a range of 100 μm×100 μm arbitrarily selected on the surface of the ceramic layer is 10-800, and the coverage rate A1 of pores with a diameter of ≥0.5 μm on the surface of the ceramic layer is 10%-50%; The electrolyte includes an organic solvent, and the organic solvent includes at least two of dimethyl carbonate, ethyl methyl carbonate, propylene carbonate, ethylene carbonate, diethyl carbonate, propyl propionate, ethyl propionate and ethyl acetate.
[0006] Through the above technical solution, the present invention has at least the following advantages compared with the prior art: The battery of the present invention has a large number of pores on the surface and / or inner layer of the ceramic layer of the diaphragm through the cooperation of the diaphragm and the electrolyte, thereby improving the porosity of the diaphragm, improving the ion conductivity, and then improving the fast charge cycle performance and rate performance of the battery. At the same time, due to the presence of a large number of pores in the diaphragm, the packing density of inorganic particles in the ceramic layer can be increased, so that the diaphragm has a high porosity while still having a high puncture strength, so that the diaphragm has the advantages of high fast charge cycle performance, high rate performance and high safety performance. In addition, the ceramic layer of the diaphragm of the present invention has adhesiveness, which can replace the glue layer to improve the stability between the diaphragm and the positive active layer and the negative active layer, thereby avoiding the adverse effect of the glue layer on the fast charge cycle performance of the battery.
[0007] Other features and advantages of the present invention will be described in detail in the following detailed description.
[0008] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article. BRIEF DESCRIPTION OF THE DRAWINGS
[0009] Figure 1 Shown is a SEM image of a ceramic layer in a diaphragm according to an embodiment of the present invention.
[0010] Figure 2 Shown is a pore size distribution curve of the diaphragm in Example 1 of the present invention.
[0011] Figure 3 Shown is a schematic cross-sectional view of the separator of the present invention.
[0012] Figure 4 Shown is a schematic top view of the diaphragm of the present invention. DETAILED DESCRIPTION
[0013] The specific embodiments of the present invention are described in detail below. It should be understood that the specific embodiments described herein are only used to illustrate and explain the present invention and are not used to limit the present invention. In this article, unless otherwise specified, the data range includes the endpoints.
[0014] It should be noted that the numerical expressions such as "first" and "second" in the present disclosure are only used to distinguish different substances or usage methods, and do not represent the difference in order.
[0015] The present invention provides a battery, wherein the battery comprises a positive electrode sheet, a negative electrode sheet, an electrolyte and a separator located between the positive electrode sheet and the negative electrode sheet, the separator comprises a substrate and a ceramic layer located on one side or both sides of the substrate, the ceramic layer comprises inorganic particles, the ceramic layer is a porous structure, the porous structure comprises pores with a diameter of ≥0.5 μm, within a range of 100 μm×100 μm arbitrarily selected on the surface of the ceramic layer, the number of pores with a diameter of ≥0.5 μm is 10-800, and the coverage rate A1 of pores with a diameter of ≥0.5 μm on the surface of the ceramic layer is 10%-50%; The electrolyte includes an organic solvent, and the organic solvent includes at least two of dimethyl carbonate, ethyl methyl carbonate, propylene carbonate, ethylene carbonate, diethyl carbonate, propyl propionate, ethyl propionate and ethyl acetate.
[0016] Figure 1 is a SEM image of the ceramic layer in the diaphragm in one embodiment of the present invention, Figure 1 It can be seen that the ceramic layer is a porous structure, and Figure 1 The red circles in the figure are holes with a diameter of ≥0.5μm. One red circle indicates one hole with a diameter of ≥0.5μm. It should be noted that the red circle only indicates the Figure 1 The pores with a diameter of ≥0.5 μm do not indicate Figure 1 All pores with a diameter ≥ 0.5 μm.
[0017] like Figure 3 and Figure 4 As shown, the diaphragm includes a substrate 1 and a ceramic layer 2 located on one side or both sides of the substrate 1. The ceramic layer 2 includes inorganic particles 21. The ceramic layer is a porous structure, and 22 is the pore of the ceramic layer.
[0018] The porous structure may include pores with a diameter ≥ 0.5 μm, and within a range of 100 μm×100 μm arbitrarily selected on the surface of the ceramic layer, the number of pores with a diameter ≥ 0.5 μm is 10-800 (for example, 10, 50, 100, 200, 300, 400, 500, 600, 700 or 800), and the coverage A1 of pores with a diameter ≥ 0.5 μm on the surface of the ceramic layer is 10%-50% (for example, 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45% or 50%).
[0019] In the present invention, the term "diameter" refers to the diameter of a single pore. For example, a pore with a diameter ≥ 0.5 μm means that a single pore has a diameter ≥ 0.5 μm; the number of pores with a diameter ≥ 0.5 μm means the number of pores with a diameter ≥ 0.5 μm.
[0020] By cooperating the diaphragm with the electrolyte and controlling the diameter of the pores in the porous structure, the number of pores with a diameter ≥ 0.5 μm, and the coverage of pores with a diameter ≥ 0.5 μm on the surface of the ceramic layer, the porosity of the diaphragm can be improved, the ion conductivity can be improved, and the fast charge cycle performance and rate performance of the battery can be improved. At the same time, the ceramic layer in the diaphragm of the present invention includes inorganic particles, and the diameter of the pores in the porous structure, the number of pores with a diameter ≥ 0.5 μm, and the coverage of pores with a diameter ≥ 0.5 μm on the surface of the ceramic layer can be controlled to increase the packing density of the inorganic particles in the ceramic layer, so that the diaphragm maintains a high puncture strength, so that the battery has a high fast charge cycle performance and rate performance while still having a high safety performance. In addition, the ceramic layer of the diaphragm of the present invention has adhesiveness, which can replace the glue layer to improve the stability between the diaphragm and the positive active layer and the negative active layer, thereby avoiding the adverse effects of the glue layer on the fast charge cycle performance of the battery.
[0021] When the number of pores with a diameter ≥0.5μm within a range of 100μm×100μm selected at random on the surface of the ceramic layer is less than 10, the ion permeability of the diaphragm is low, and the fast charging cycle and rate performance of the battery cannot be effectively improved; when the number of pores with a diameter ≥0.5μm within a range of 100μm×100μm selected at random on the surface of the ceramic layer is higher than 800, the heat resistance of the diaphragm is low, and the safety performance of the battery cannot be effectively improved.
[0022] When the coverage rate A1 of pores with a diameter ≥ 0.5 μm on the surface of the ceramic layer is lower than 10%, the ion permeability of the diaphragm is insufficient to effectively improve the fast charging cycle and rate performance of the battery; when the coverage rate A1 of pores with a diameter ≥ 0.5 μm on the surface of the ceramic layer is higher than 50%, the heat resistance of the diaphragm is insufficient to effectively improve the safety performance of the battery.
[0023] In the present invention, the diameter of the pores in the porous structure, the number of pores with a diameter ≥ 0.5 μm, and the coverage of pores with a diameter ≥ 0.5 μm on the surface of the ceramic layer are controlled by the cooperation of the diaphragm and the electrolyte. Compared with the prior art, the battery has a higher fast charge cycle performance and a higher rate performance without affecting the safety performance of the battery. In order to further improve the effect, one or more of the technical features can be further optimized.
[0024] The diaphragm and battery of the present invention can be prepared by the following method: Preparation of the initial diaphragm: Inorganic particles, water or deionized water, a thickener and a diaphragm binder are mixed to prepare an aqueous slurry, a polymer is added to the aqueous slurry to prepare a ceramic slurry, and the ceramic slurry is coated on one or both sides of the substrate to prepare the initial diaphragm. The initial diaphragm includes a substrate and a ceramic layer located on one or both sides of the substrate, and the ceramic layer includes inorganic particles and a polymer.
[0025] In one example, the thickener includes one or more of methyl cellulose (CMC), sodium carboxymethyl cellulose (CMC-Na), and lithium carboxymethyl cellulose (CMC-Li).
[0026] In one example, the membrane binder includes one or more of polytetrafluoroethylene, polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene, polyimide, polyacrylonitrile, polymethyl (meth)acrylate, aramid resin, poly (meth)acrylic acid, styrene-butadiene rubber (SBR), polyvinyl alcohol, polyvinyl acetate and carboxyethyl cellulose.
[0027] In one example, the weight ratio of the inorganic particles, the thickener, and the membrane binder is (85%-98%): (1%-5%): (1%-10%).
[0028] In one example, the weight ratio of the polymer to the inorganic particles is (1%-20%):(99%-80%). It is understood that the weight content of the polymer can be in the range of 1%-20% (e.g., 1%, 5%, 10%, 15% or 20%), and the weight content of the inorganic particles can be in the range of 99%-80% (e.g., 99%, 95%, 90%, 85%, 80%).
[0029] The polymer may include a first monomer and a second monomer. The polymer has adhesive properties and can replace the coating layer to improve the stability between the separator and the positive electrode active layer and the negative electrode active layer, thereby avoiding the adverse effect of the coating layer on the fast charge cycle performance of the battery.
[0030] In one example, the first monomer includes one or more of an acrylonitrile monomer, a styrene monomer, and an acrylate monomer.
[0031] In one example, the acrylic acid ester monomer includes one or more of methyl methacrylate, methyl acrylate, ethyl acrylate, butyl acrylate, isooctyl acrylate, lauryl acrylate, and octadecyl acrylate.
[0032] In one example, the styrene monomer includes one or more of styrene, methylstyrene, triphenylethylene and 4-methylstyrene.
[0033] In one example, the acrylonitrile monomer includes one or more of acrylonitrile, triphenylacrylonitrile, 3-cyclopentylacrylonitrile and 3,3-(diphenyl)acrylonitrile.
[0034] In one example, the second monomer includes one or more of acrylic acid, butadiene, methacrylic acid, acrylamide, hydroxymethyl acrylamide, hydroxyethyl acrylamide, isopropyl acrylamide, glycidyl (meth)acrylate, and allyl glycidyl ester.
[0035] At 60°C-90°C, the polymer can be immersed in the solvent for 2min-10min, and the polymer is completely dissolved. Due to this characteristic of the polymer, during the hot pressing process of the battery, the polymer is completely dissolved and a large number of pores are formed in the ceramic layer of the separator.
[0036] The solvent may be the organic solvent described in the present invention, or may be the electrolyte solution comprising the organic solvent described in the present invention.
[0037] Preparation of the battery: Assemble the initial separator with a positive electrode sheet (a conventional positive electrode sheet in the art), a negative electrode sheet (a conventional negative electrode sheet in the art) and an electrolyte to form a battery, wherein the electrolyte may include an organic solvent, and the organic solvent includes at least two of dimethyl carbonate, ethyl methyl carbonate, propylene carbonate, ethylene carbonate, diethyl carbonate, propyl propionate, ethyl propionate and ethyl acetate.
[0038] The prepared battery is hot pressed, wherein the hot pressing conditions include: a hot pressing temperature of 60°C-90°C (for example, 60°C, 65°C, 70°C, 75°C, 80°C, 85°C or 90°C), a hot pressing pressure of 0.1MPa-1.5MPa (for example, 0.1MPa, 0.3MPa, 0.5MPa, 0.8MPa, 1MPa, 1.3MPa or 1.5MPa), and a hot pressing time of 10min-60min (10min, 20min, 30min, 40min, 50min or 60min).
[0039] In the battery after hot pressing, since the polymer is completely dissolved in the electrolyte including the organic solvent, there is no polymer in the ceramic layer of the separator. The completely dissolved polymer forms a large number of pores in the middle and / or on the surface of the ceramic layer, and the separator including a large number of pores of the present invention is obtained. In the process of preparing batteries, hot pressing is an indispensable step in preparing batteries, which can also be called formation in the art.
[0040] The glue layer in the prior art has adhesive properties, and during the preparation of the battery, it can improve the stability between the diaphragm and the positive electrode active layer and the negative electrode active layer, ensuring that the battery core will not become soft and affect the process efficiency of the battery. However, during the use of the battery, the glue layer will reduce the fast charging cycle performance of the battery. In the diaphragm in the battery of the present invention, during the preparation of the battery, the ceramic layer in the diaphragm includes a polymer, and the polymer has adhesive properties, which can replace the glue layer to improve the stability between the diaphragm and the positive electrode active layer and the negative electrode active layer. During the use of the battery (which has been hot pressed), the polymer is completely dissolved in the electrolyte including the above-mentioned organic solvent, avoiding the adverse effects of the polymer on the fast charging cycle performance of the battery.
[0041] In one example, the average particle size of the polymer is 0.5 μm-10 μm (eg, 0.5 μm, 1 μm, 2 μm, 3 μm, 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, or 10 μm).
[0042] In one example, the average particle size of the polymer is 1 μm-8 μm.
[0043] In the present invention, the average particle size can be measured by a laser particle size analyzer. For example, the average particle size of the polymer, the average particle size of the primary particles, the average particle size of the secondary particles, and the average particle size of the inorganic particles can all be measured by a laser particle size analyzer.
[0044] In one example, the polymer includes primary particles and / or secondary particles formed by agglomeration of the primary particles.
[0045] In one example, the polymer satisfies the following relationship: D4≤2×D3, where D3 is the average particle size of the primary particles, in μm, and D4 is the average particle size of the secondary particles, in μm. Controlling the polymer to satisfy the above relationship can make the polymer have better dispersibility, so that the pores formed by the polymer have better consistency, so that the current at each pole piece of the battery during the charge and discharge process has better consistency, thereby improving the charge and discharge performance of the battery.
[0046] In one example, the average particle size D3 of the primary particles is 0.5 μm-5 μm (eg, 0.5 μm, 1 μm, 2 μm, 3 μm, 4 μm or 5 μm).
[0047] In one example, the diaphragm satisfies the following relationship: D5≤4×D6, wherein D5 is the diameter of the largest hole in the pores with a diameter ≥0.5μm in the range of 100μm×100μm selected at random on the surface of the ceramic layer, in μm, and D6 is the diameter of the smallest hole in the pores with a diameter ≥0.5μm in the range of 100μm×100μm selected at random on the surface of the ceramic layer, in μm. Controlling the diaphragm to satisfy the above relationship can make the pores in the ceramic layer have better consistency, so that the current at each location of the electrode during the charge and discharge process of the battery has better consistency, thereby improving the charge and discharge performance of the battery.
[0048] In one example, the number of holes with a diameter of ≥0.5 μm in an area of 100 μm×100 μm randomly selected on the surface of the ceramic layer is 50-500.
[0049] In one example, the coverage rate A1 of the pores with diameters ≥ 0.5 μm on the surface of the ceramic layer is 15%-45%.
[0050] The coverage rate A1 of the pores with diameter ≥0.5 μm on the ceramic layer surface represents the ratio of the sum of the orthographic projection areas of the pores with diameter ≥0.5 μm on the ceramic layer surface on the substrate surface to the orthographic projection area of the ceramic layer on the substrate surface.
[0051] In the present invention, the coverage of the pores with a diameter of ≥0.5 μm on the surface of the ceramic layer can be obtained by testing in the following manner: for example, by using a scanning electron microscope (SEM) test, specifically: using SEM to obtain a microscopic image of the surface of the ceramic layer, randomly dividing an area of 100 μm in the image 2 Take an area (for example, 100µm×100µm), divide this area into 100*100 uniform squares, if the coverage area of the holes with diameter ≥0.5μm in the square exceeds half of the square area, it means that the square is occupied by holes with diameter ≥0.5μm, otherwise it means that the square is not occupied by holes with diameter ≥0.5μm, count the number of squares occupied by holes with diameter ≥0.5μm, record the total number of squares occupied by holes with diameter ≥0.5μm as X, then coverage = (X / 100*100)*100%, repeat the above operation 5 times, and take the average value of the 5 times as the coverage of holes with diameter ≥0.5μm on the surface of the ceramic layer.
[0052] According to a specific embodiment, within a range of 100 μm×100 μm arbitrarily selected on the surface of the ceramic layer, the number of holes with a diameter ≥ 0.5 μm is 50-500, and the coverage rate A1 of holes with a diameter ≥ 0.5 μm on the surface of the ceramic layer is 15%-45%.
[0053] In one example, the inorganic particles include one or more of aluminum oxide, boehmite, magnesium oxide, magnesium hydroxide, barium sulfate, barium titanate, zinc oxide, calcium oxide, silicon dioxide, silicon carbide, and boron nitride.
[0054] In one example, the diaphragm satisfies the following relationship: 1<D1 / D2<20 (for example, 1.1, 3, 5, 8, 10, 13, 15, 18 or 19.9), wherein D1 is the average diameter of the pores of the ceramic layer with a diameter ≥ 0.5 μm, in μm; D2 is the average particle size of the inorganic particles, in μm. Controlling the diaphragm to satisfy the above relationship can, on the one hand, allow a large number of pores to exist in the diaphragm, further improve the porosity of the diaphragm, thereby further improving the ion transport performance of the diaphragm and further improving the fast charge cycle performance of the battery; on the other hand, it can further improve the packing density between the inorganic particles, thereby further improving the puncture strength and thermal stability of the diaphragm, thereby reducing the self-discharge of the battery, improving the safety performance of the battery, and leaving the self-discharge and safety performance of the battery unaffected. When D1 / D2≤1, the packing density between the inorganic particles is too low, the thermal stability of the diaphragm is poor, thereby reducing the safety performance of the battery, and the average diameter of the pores with a diameter ≥0.5μm is too small, resulting in a decrease in the rate performance of the battery; when D1 / D2≥20, the pore diameter is too large, the thermal stability of the diaphragm is poor, thereby reducing the safety performance of the battery, and the average particle size of the inorganic particles is too small, resulting in a decrease in the rate performance of the battery.
[0055] In the present invention, the term "diameter" has different meanings from "average diameter". The term "average diameter" refers to the average value of the diameters of all pores in a system. For example, the average diameter of pores with a diameter of ≥ 0.5 μm in a ceramic layer represents the average value of the diameters of all pores with a diameter of ≥ 0.5 μm in a system.
[0056] Both the diameter and the average diameter can be obtained by SEM testing. For example, it can be obtained by testing in the following manner: using an electrolytic emission scanning electron microscope (S-3400N manufactured by Hitachi, Ltd.), observe the surface of the ceramic layer at a magnification of 50,000 times. The image size at this time is 2.5μm×1.8μm. It should be noted that the number of pixels is 1,280 pixels×960 pixels, and the size of 1 pixel is 2nm×1.9nm. For the diameter, a square or rectangle with the smallest area that completely surrounds one hole is drawn on the obtained image, that is, a square or rectangle in which the end of the hole is connected to the four sides of the square or rectangle. In the case of a square, the length of one side is set as the diameter of the hole, and in the case of a rectangle, the length of the long side (major axis diameter) is set as the diameter of the hole. For any 81 holes, the diameter of each hole is measured, and the average value of the number is set as the average diameter. It should be noted that when more than 81 holes are observed in the captured image, the number average of any 81 holes in the image is set as the average diameter of the holes. When 81 holes are not observed in the image, multiple images are captured and the number average of the total 81 holes is set as the average diameter.
[0057] In one example, 2≤D1 / D2≤15.
[0058] In one example, D1 is 0.5 μm-10 μm (eg, 0.5 μm, 1 μm, 2 μm, 3 μm, 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, or 10 μm).
[0059] In one example, D1 is 1 μm-8 μm.
[0060] In one example, D2 is 0.1 μm-3 μm (eg, 0.1 μm, 0.5 μm, 1 μm, 1.5 μm, 2 μm, 2.5 μm, or 3 μm).
[0061] In one example, D2 is 0.5 μm-2 μm.
[0062] According to a specific implementation, D1 is 1 μm-8 μm, D2 is 0.5 μm-2 μm, and the diaphragm satisfies the following relationship: 2≤D1 / D2≤15.
[0063] In one example, the coverage of the ceramic layer on the surface of the substrate is 55%-100% (e.g., 55%, 60%, 70%, 80%, 90% or 100%). Controlling the coverage of the ceramic layer on the surface of the substrate within the above range can make the diaphragm have good thermal stability, thereby making the battery have excellent safety performance. When the coverage of the ceramic layer on the surface of the substrate is less than 55%, the thermal stability of the diaphragm is poor, thereby reducing the safety performance of the battery.
[0064] In the present invention, the coverage of the ceramic layer on the substrate surface refers to the ratio of the orthographic projection area of the ceramic layer on the substrate surface to the substrate surface area. Figure 1 As shown, the holes in the porous structure will partially expose the substrate, while partially will not expose the substrate, and the orthographic projection area of the ceramic layer on the surface of the substrate will exclude the area of the holes exposed by the substrate.
[0065] In one example, the coverage rate of the ceramic layer on the surface of the substrate is 60%-90%.
[0066] In one example, based on the total volume of the pores in the ceramic layer, the volume proportion of pores with a diameter of ≥0.5 μm is 20%-80% (for example, 20%, 30%, 40%, 50%, 60%, 70% or 80%). Controlling the volume proportion of pores with a diameter of ≥0.5 μm in the total volume of the pores in the ceramic layer within the above range can, on the one hand, enable the diaphragm to have good heat resistance, thereby improving the safety performance of the battery; on the other hand, it can increase the porosity of the diaphragm, so that the diaphragm has good ion permeability, thereby improving the fast charge cycle and rate performance of the battery. When the volume proportion of pores with a diameter of ≥0.5 μm in the total volume of the pores in the ceramic layer is less than 20%, the porosity of the diaphragm is low, so that the ion permeability of the diaphragm is insufficient, and the fast charge cycle and rate performance of the battery cannot be effectively improved; when the volume proportion of pores with a diameter of ≥0.5 μm in the total volume of the pores in the ceramic layer is higher than 80%, the heat resistance of the diaphragm is low, and the safety performance of the battery cannot be guaranteed.
[0067] In the present invention, the volume fraction of pores with a diameter of ≥0.5 μm can be obtained by testing in the following manner: a mercury intrusion testing method can be used, specifically, a mercury intrusion testing method is used to obtain a pore size distribution curve of the entire diaphragm (such as Figure 2 As shown in the figure), the pore size of the substrate layer in the diaphragm does not exceed 0.08μm. Therefore, the pore size distribution curve of the ceramic layer can be obtained by eliminating the pore sizes ≤0.08μm in the pore size distribution curve of the diaphragm in the pore size distribution curve of the overall diaphragm. The ratio of the integral area of pores greater than or equal to 0.5μm in the pore size distribution curve of the ceramic layer to the total integral area of the pore size distribution curve of the ceramic layer is calculated, which is the volume proportion of pores with a diameter ≥0.5μm in the total volume of pores in the ceramic layer.
[0068] In one example, based on the total volume of the pores in the ceramic layer, the volume of pores with a diameter of ≥0.5 μm accounts for 30%-60%.
[0069] In one example, the thickness H1 of the ceramic layer is 1 μm-5 μm (for example, 1 μm, 2 μm, 3 μm, 4 μm or 5 μm). It is understandable that in the process of preparing the diaphragm, the thickness of the ceramic layer cannot be absolutely uniform, so in the present invention, the thickness H1 of the ceramic layer is the maximum thickness of the ceramic layer. The thickness of the ceramic layer can be obtained by SEM testing.
[0070] In one example, H1 is 1.5 μm-4 μm.
[0071] In one example, the porosity K1 of the ceramic layer is 30%-80% (for example, 30%, 40%, 50%, 60%, 70% or 80%). Controlling the porosity K1 of the ceramic layer within the above range can, on the one hand, enable the diaphragm to have good heat resistance, thereby improving the safety performance of the battery; on the other hand, enable the diaphragm to have good ion permeability, thereby improving the fast charge cycle and rate performance of the battery. When the porosity K1 of the ceramic layer is lower than 30%, the ion permeability of the diaphragm is low, and the fast charge cycle and rate performance of the battery cannot be effectively improved; when the porosity K1 of the ceramic layer is higher than 80%, the heat resistance of the diaphragm is low, and the safety performance of the battery cannot be guaranteed.
[0072] In one example, the porosity K1 of the ceramic layer is 40%-70%.
[0073] In the present invention, the porosity can be measured and obtained in the following manner: porosity of ceramic layer = (1-(surface density of ceramic layer / thickness of ceramic layer) / density of inorganic particles)*100%.
[0074] According to a specific embodiment, the ceramic layer is a porous structure, and the porous structure includes pores with a diameter of ≥0.5μm. In the range of 100μm×100μm arbitrarily selected on the surface of the ceramic layer, the number of pores with a diameter of ≥0.5μm is 50-500, the coverage rate A1 of pores with a diameter of ≥0.5μm on the surface of the ceramic layer is 15%-45%, and the average diameter D1 of pores with a diameter of ≥0.5μm in the ceramic layer is 1μm-8μm. Based on the total volume of pores in the ceramic layer, the volume of pores with a diameter of ≥0.5μm accounts for 30%-60%. Controlling the range of the above-mentioned technical features of the ceramic layer can make the porosity K1 of the ceramic layer meet 40%-70%, thereby improving the performance of the diaphragm in conducting ions, and improving the rate performance and fast charging cycle performance of the battery.
[0075] In one example, the ceramic layer further includes a membrane binder and a thickener.
[0076] In one example, based on the total weight of the ceramic layer, the weight content of the inorganic particles is 85%-98% (for example, 85%, 86%, 87%, 88%, 89%, 90%, 91%, 92%, 93%, 94%, 95%, 96%, 97% or 98%), the weight content of the diaphragm binder is 1%-10% (for example, 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9% or 10%), and the weight content of the thickener is 1%-5% (for example, 1%, 2%, 3%, 4% or 5%).
[0077] In one embodiment, the surface density of the ceramic layer is 1 g / m 2 -8g / m 2 (For example, 1g / m 2 , 2g / m 2 , 3g / m 2 , 4g / m 2 , 5g / m 2 , 6g / m 2 , 7g / m 2 or 8g / m 2 ).
[0078] In one embodiment, the surface density of the ceramic layer is 1.5 g / m 2 -6g / m 2 .
[0079] In the present invention, the surface density refers to the single-sided surface density. For example, the surface density of the ceramic layer refers to the surface density of the side (i.e., the side with the ceramic layer) when there is a ceramic layer on the surface of one side of the substrate; when there are ceramic layers on the surfaces of both sides of the substrate, the surface densities of the ceramic layers on both sides of the diaphragm are the same, and the surface density of the ceramic layer is the surface density of any one side.
[0080] In one example, the organic solvent includes a first solvent and a second solvent.
[0081] In one example, the first organic solvent includes one or more of dimethyl carbonate, ethyl methyl carbonate, diethyl carbonate, propyl propionate, ethyl propionate and ethyl acetate.
[0082] In one example, the second organic solvent includes propylene carbonate and / or ethylene carbonate.
[0083] In one example, the weight ratio of the first organic solvent to the weight ratio of the second organic solvent is (0.05-20):1 (for example, 0.05, 0.1, 0.5, 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19 or 20). Controlling the weight ratio of the first organic solvent to the weight ratio of the second organic solvent within the above range can make the electrolyte have a suitable viscosity and good ionic conductivity, so that the battery has a higher long cycle performance and better fast charge cycle performance. When the weight ratio of the first organic solvent to the weight ratio of the second organic solvent is lower than 0.05:1, the content of the second organic solvent is too high, resulting in too high viscosity of the electrolyte, which reduces the fast charge cycle performance of the battery; when the weight ratio of the first organic solvent to the weight ratio of the second organic solvent is higher than 20:1, the content of the first organic solvent is too high, resulting in low ionic conductivity, which reduces the long cycle performance of the battery.
[0084] In one example, the weight ratio of the first organic solvent to the second organic solvent is (0.1-10):1.
[0085] In another example, the organic solvent includes ethyl methyl carbonate, ethyl acetate, and propylene carbonate.
[0086] In one example, the weight ratio of ethyl methyl carbonate, ethyl acetate and propylene carbonate in the organic solvent is (10%-70%):(10%-70%):(15%-40%).
[0087] It can be understood that the weight content of ethyl methyl carbonate in the organic solvent can be in the range of 10%-70% (for example, 10%, 20%, 30%, 40%, 50%, 60% or 70%), the weight content of ethyl acetate in the organic solvent can be in the range of 10%-70% (for example, 10%, 20%, 30%, 40%, 50%, 60% or 70%), and the weight content of propylene carbonate in the organic solvent can be in the range of 15%-40% (for example, 15%, 20%, 25%, 30%, 35% or 40%), but it needs to be satisfied that the sum of the weight content of ethyl methyl carbonate, the weight content of ethyl acetate and the weight content of ethylene carbonate in the organic solvent is 100%.
[0088] In one example, based on the total weight of the electrolyte, the weight content of the organic solvent is 70%-86% (eg, 70%, 73%, 75%, 78%, 80%, 85% or 86%).
[0089] In one example, based on the total weight of the electrolyte, the weight content of the organic solvent is 75%-81%.
[0090] In one example, the electrolyte further includes LiFSI and optionally an additive.
[0091] In one example, the additive includes one or more of fluoroethylene carbonate (FEC), 1,3-propane sultone (PS), vinylene carbonate (VC), lithium difluorophosphate (LiPO2F2), lithium bis(oxalatoborate) (LiBOB), lithium difluorooxalatoborate (LiODFB), lithium difluorooxalatophosphate (LiODFP), lithium tetrafluoroborate (LiBF4) and lithium tetrafluorooxalatophosphate (LiTFOP).
[0092] In one example, based on the total weight of the electrolyte, the weight content of LiFSI is 2%-20% (e.g., 2%, 5%, 10%, 15% or 20%), and the weight content of the additive is 0%-10%. When the weight content of the additive in the electrolyte is 0%, it means that there is no additive in the electrolyte.
[0093] In one example, based on the total weight of the electrolyte, the weight content of LiFSI is 3%-9%, and the weight content of the additive is 1%-8%.
[0094] In one example, the electrolyte further includes a lithium salt.
[0095] In one example, the lithium salt includes at least one of lithium hexafluorophosphate, lithium tetrafluoroborate, and lithium perchlorate.
[0096] In one example, based on the total weight of the electrolyte, the weight content of the lithium salt is 12%-30% (eg, 12%, 15%, 18%, 20%, 22%, 25%, 28% or 30%).
[0097] In one example, based on the total weight of the electrolyte, the weight content of the lithium salt is 15%-25%.
[0098] The battery may further include a positive electrode sheet and a negative electrode sheet.
[0099] The positive electrode sheet may be a conventional positive electrode sheet in the art. For example, the positive electrode sheet includes a positive electrode current collector and a positive electrode active layer located on at least one surface of the positive electrode current collector.
[0100] There is no special restriction on the positive electrode active layer, and the positive electrode active layer may include components such as positive electrode active material, positive electrode conductive agent, positive electrode binder, etc. according to the conventional composition in the art. Among them, the components such as positive electrode active material, positive electrode conductive agent, positive electrode binder, etc. may be selected from conventional materials in the art, for example, the positive electrode active material may be selected from one or more of lithium nickel oxide, lithium titanate, lithium cobalt oxide, lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, lithium iron phosphate, and lithium manganese oxide; the positive electrode conductive agent may be selected from one or more of conductive carbon black, carbon nanotubes, conductive graphite, and graphene; the positive electrode binder may be selected from one or more of polyvinylidene fluoride (PVDF), acrylic acid-modified PVDF, polyacrylate polymers, polytetrafluoroethylene, perfluorosulfonic acid ionomers, polyacrylonitrile, polyimide, styrene-butadiene rubber, and styrene-acrylic rubber.
[0101] In one example, the positive electrode active material is selected from lithium iron phosphate or lithium iron phosphate doped and coated with two or more elements of Al, Mg, Mn, Cr, Ti, and Zr.
[0102] In one example, based on the total weight of the positive electrode active layer, the weight content of the positive electrode active material is 90%-98% (for example, 90%, 91%, 92%, 93%, 94%, 95%, 96%, 97% or 98%), the weight content of the positive electrode conductor is 0.5%-5% (for example, 0.5%, 1%, 2%, 3%, 4% or 5%), and the weight content of the positive electrode binder is 1%-5% (for example, 1%, 2%, 3%, 4% or 5%).
[0103] The negative electrode sheet can be a conventional negative electrode sheet in the art, for example, the negative electrode sheet includes a negative electrode current collector and a negative electrode active layer coated on one side or both sides of the negative electrode current collector, and the negative electrode active layer includes a negative electrode active material, a negative electrode conductive agent and a negative electrode binder; the negative electrode active material can adopt negative electrode active materials for batteries known in the art, such as one or more of carbon-based materials, silicon-based materials, tin-based materials, and titanium-based materials; specifically, it can be one or more of artificial graphite, natural graphite, soft carbon, hard carbon, elemental silicon, silicon oxide compounds (such as SiOx / C), silicon-carbon composites (such as Si / C), silicon-nitrogen composites, silicon alloys, elemental tin, tin oxide compounds, tin alloys, elemental titanium, titanium oxide compounds, and titanium alloys.
[0104] According to a specific embodiment, the negative electrode active material is selected from one or more of artificial graphite, hard carbon, SiOx / C and Si / C.
[0105] In one example, the negative electrode conductive agent is one or more of conductive carbon black, carbon nanotubes (eg, single-walled carbon nanotubes and multi-walled carbon nanotubes), conductive graphite, and graphene.
[0106] In one example, the negative electrode binder is one or more of polyvinylidene fluoride (PVDF), acrylic acid-modified PVDF, polyacrylate polymers, polytetrafluoroethylene, perfluorosulfonic acid ionomers, polyacrylonitrile, polyimide, styrene-butadiene rubber, and styrene-acrylic rubber.
[0107] In one example, based on the total weight of the negative electrode active layer, the weight content of the negative electrode active material is 90%-98% (for example, 90%, 91%, 92%, 93%, 94%, 95%, 96%, 97% or 98%), the weight content of the negative electrode conductive agent is 0%-5% (for example, 0%, 0.1%, 0.5%, 1%, 2%, 3%, 4% or 5%), and the weight content of the negative electrode binder is 1%-5% (for example, 1%, 2%, 3%, 4% or 5%). When the weight content of the negative electrode conductive agent in the negative electrode active material layer is 0%, it means that there is no negative electrode conductive agent in the negative electrode active material layer.
[0108] The battery may be a lithium ion secondary battery.
[0109] The battery of the present invention has high rate performance and good fast charge cycle performance.
[0110] The present invention will be described in detail below by way of examples. The examples described in the present invention are only a part of the examples of the present invention, rather than all of the examples. Based on the examples in the present invention, all other examples obtained by ordinary technicians in the field without creative work are within the scope of protection of the present invention.
[0111] The following examples are provided to illustrate the separator and battery of the present invention.
[0112] Example 1 (1) Preparation of diaphragm Component preparation: Substrate: polyethylene, thickness 9 μm; Ceramic layer: inorganic particles: aluminum oxide; thickener: sodium carboxymethyl cellulose; diaphragm binder: poly (meth) acrylic acid; polymer: methyl methacrylate-acrylic acid copolymer; wherein the weight ratio of the inorganic particles, the thickener and the diaphragm binder is 92%:3%:5%; the weight ratio of the polymer to the inorganic particles is 7%:93%.
[0113] Inorganic particles, water, a thickener and a membrane binder are mixed to prepare an aqueous slurry (with a solid content of 28%), a polymer is added to the aqueous slurry to prepare a ceramic slurry, and the ceramic slurry is coated on both sides of a substrate to prepare an initial membrane.
[0114] (2) Preparation of electrolyte Ingredients preparation: Lithium salt: lithium hexafluorophosphate, 12.5 parts by weight; Organic solvent: 76.5 parts by weight, wherein the weight ratio of ethyl methyl carbonate (EMC), ethyl acetate (EA) and propylene carbonate (PC) is 35%:35%:30%; LiFSi, 6.5 parts by weight; Additives: vinylene carbonate (VC), 4.5 parts by weight; In a glove box filled with argon (water content <10ppm, oxygen content <1ppm), the organic solvents were mixed evenly to obtain a mixed solution 1, additives were added to the mixed solution 1 to obtain a mixed solution 2, LiFSi and lithium salt were slowly added to the mixed solution 2, and the mixture was stirred evenly to obtain a non-aqueous electrolyte.
[0115] (3) Preparation of positive electrode The positive electrode active material (lithium iron phosphate (LFP) doped with titanium and vanadium), the positive electrode binder (polyvinylidene fluoride (PVDF)), and the positive electrode conductive agent (acetylene black) are mixed in a weight ratio of 96.5:1.5:2.0, N-methylpyrrolidone (NMP) is added, and the mixture is stirred under the action of a vacuum mixer until the mixed system becomes a positive electrode slurry with uniform fluidity; the positive electrode slurry is evenly coated on the surface of both sides of an aluminum foil with a thickness of 10 μm; the coated aluminum foil is baked in an oven with 5 different temperature gradients (95℃±5℃, 100℃±5℃, 103℃±5℃, 100℃±5℃, 95℃±5℃), and then dried in an oven at 120℃ for 8 hours, and then rolled and cut to obtain the required positive electrode sheet.
[0116] (4) Preparation of negative electrode The negative electrode active material (artificial graphite), the negative electrode conductive agent (including 0.2 parts by weight of single-walled carbon nanotubes (SWCNT) and 1 part by weight of conductive carbon black (SP)), and the negative electrode binder (including 1 part by weight of sodium carboxymethyl cellulose (CMC-Na) and 2.5 parts by weight of styrene-butadiene rubber (SBR)) are mixed in a weight ratio of 95.3:1.2:3.5, and a slurry is prepared by a wet process (water is added to the mixture formed by the above mixing, and the mixture is stirred under the action of a vacuum stirrer until the mixture becomes a negative electrode slurry with uniform fluidity), and the slurry is coated on the surfaces of both sides of the negative electrode current collector (copper foil), and the negative electrode sheet is obtained by drying (temperature: 85°C, time: 5h), rolling and die-cutting.
[0117] (5) Preparation of lithium-ion secondary batteries The positive electrode sheet of step (3), the separator of step (1), and the negative electrode sheet of step (4) are wound to obtain a bare cell without liquid injection, and 5MPa is applied to the wound core for 10 minutes; the bare cell is placed in an outer packaging foil, and the electrolyte of step (2) is injected into the dried bare cell, and the process includes vacuum packaging, standing, hot pressing (wherein the hot pressing temperature is 80°C, the hot pressing pressure is 1MPa, and the hot pressing time is 40 minutes. After hot pressing, the first polymer in the initial separator is partially dissolved, and the second polymer is completely dissolved. The partially dissolved first polymer and the completely dissolved second polymer form a large number of pores in the middle and surface of the ceramic layer of the separator to obtain the separator of the present invention), shaping, sorting, etc., to obtain the desired lithium ion secondary battery. Wherein, the separator after hot pressing, based on the total weight of the ceramic layer, has a weight content of inorganic particles of 92%, a weight content of separator binder of 5%, and a weight content of thickener of 3%.
[0118] Example 2 The method is carried out in accordance with Example 1, except that the weight of the organic solvent remains unchanged, and the organic solvent is adjusted to consist of a first organic solvent (EMC) and a second organic solvent (PC), wherein the weight ratio of the first organic solvent to the second organic solvent is 1:1.
[0119] Example 3 This embodiment is used to illustrate that different parameter value combinations can still achieve the effects of the present invention.
[0120] This example is carried out with reference to Example 1, and specifically see Table 1-1 and Table 1-2.
[0121] Example 4 This embodiment is used to illustrate that different parameter value combinations can still achieve the effects of the present invention.
[0122] Refer to Example 2, and see Table 1-1 and Table 1-2 for details.
[0123] Example 5 Group This group of examples is used to illustrate the impact produced when the number of pores with a diameter ≥ 0.5 μm is changed.
[0124] This example group was carried out with reference to Example 1, except that the number of holes with a diameter ≥ 0.5 μm was changed, as shown in Table 1-1 and Table 1-2 for details.
[0125] Example 6 Group This group of embodiments is used to illustrate the impact produced when D2 changes.
[0126] This embodiment group is carried out with reference to embodiment 1, except that D2 is changed, see Table 1-1 and Table 1-2 for details.
[0127] Example 7 Group This set of examples is intended to illustrate the effects of varying the specific selection of polymer.
[0128] This example group was carried out with reference to Example 1, except that the polymer was changed, as shown in Table 1-1 and Table 1-2 for details.
[0129] Example 8 Group This group of examples is used to illustrate the impact produced when the coverage of the ceramic layer on the substrate surface changes.
[0130] This example group is carried out with reference to Example 1, except that the coverage of the ceramic layer on the substrate surface is changed by adjusting the weight ratio of the polymer to the weight of the inorganic particles, as shown in Table 1-1 and Table 1-2 for details.
[0131] Example 9 Group This group of embodiments is used to illustrate the impact of changing the weight ratio of EMC / EA / PC.
[0132] This example group was carried out with reference to Example 1, except that the weight ratio of EMC / EA / PC was changed, as shown in Table 1-1 and Table 1-2 for details.
[0133] Example 10 Group This group of examples is used to illustrate the influence produced when the weight ratio of the first organic solvent to the second organic solvent is changed.
[0134] This example group was carried out with reference to Example 2, except that the weight ratio of the first organic solvent to the second organic solvent was changed, as shown in Table 1-1 and Table 1-2 for details.
[0135] Embodiment 11 This example group was carried out with reference to Example 1, except that the relationship between D5 and D6 was changed by adjusting the particle size distribution of the polymer primary particles, as shown in Table 1-1 and Table 1-2.
[0136] Example 12 This set of examples is used to illustrate the effects produced when the specific selection of the organic solvent is changed.
[0137] This example group was carried out with reference to Example 1, except that the specific selection of the organic solvent was changed, as shown in Table 1-1 and Table 1-2.
[0138] Comparative Example 1 The process is carried out in accordance with Example 1, except that the number of holes with a diameter ≥ 0.5 μm is changed. For details, see Table 1-1 and Table 1-2.
[0139] Comparative Example 2 The process is carried out in accordance with Example 1, except that the number of holes with a diameter ≥ 0.5 μm is changed. For details, see Table 1-1 and Table 1-2.
[0140] Comparative Example 3 Component preparation: Substrate: polyethylene, thickness 9 μm; Ceramic layer: inorganic particles: aluminum oxide (1 μm); thickener: sodium carboxymethyl cellulose; diaphragm binder: poly (meth) acrylic acid; wherein the weight ratio of the inorganic particles, the thickener and the diaphragm binder is 92%:3%:5%.
[0141] Inorganic particles, water, thickener and membrane binder are mixed to prepare an aqueous slurry (with a solid content of 28%), and the aqueous slurry is coated on both sides of the substrate. The thickness of the ceramic layer is 2 μm, and the surface density of the ceramic layer is 3.4 g / m 2 .
[0142] Table 1-1 *Same as Example 1.
[0143] Table 1-2 *Same as Example 1.
[0144] Test Case The diaphragms and lithium-ion secondary batteries obtained in the examples and comparative examples were tested as follows: (1) Diaphragm shrinkage test Take a diaphragm sample of 15cm*15cm length, pierce two holes with a diameter of 0.5mm at an interval of 10cm along the length direction of the diaphragm, and bake the sample in an oven at 150±2℃ for 1h. The distance between the two holes before baking is L1, and the distance between the two holes after baking is L2. Thermal shrinkage = (L1-L2) / L1*100%.
[0145] (2) 130℃ and 150℃ furnace temperature test The lithium-ion secondary battery is heated in a convection air box at a starting temperature of (25±3)℃, a temperature change rate of (5±2)℃ / min, and the temperature is raised to (130±2)℃ and (150±2)℃ respectively. The test is terminated after 60 minutes of holding, and the battery status at (130±2)℃ and (150±2)℃ is recorded respectively. There are 30 batteries in each sample. If there is no explosion and / or fire, it means "pass", and if there is explosion or fire, it means "fail". The result is expressed as "number of passes / 30", for example, "30 / 30" means that all batteries have passed, and "10 / 30" means that 10 batteries out of 30 batteries have failed. It should be noted that the test result of "30 / 30" at a furnace temperature of 130℃ indicates that the safety performance of the lithium-ion secondary battery is not affected.
[0146] (3) Fast charging cycle test Place the lithium-ion secondary battery in a (25±2)℃ environment and let it stand for 2-3 hours. When the battery body reaches (25±2)℃, charge the battery at 5C constant current with a cutoff current of 0.05C. After the battery is fully charged (100% SOC), let it sit for 5 minutes, and then discharge it at 10C constant current to a cutoff voltage of 2.2V. Record the highest discharge capacity of the first 3 cycles as the initial capacity Q. When the cycle reaches 1000 times, record the last discharge capacity of the battery Q1. Capacity retention rate (%) = Q1 / Q×100%.
[0147] (4) Rate performance test Place the lithium-ion secondary battery at 25℃±2℃ for 4h, discharge it to 2.2V at 0.5C, charge it to the upper limit voltage (3.65V) at 0.5C, and record the cell capacity Q2; discharge the fully charged cell at 10C constant current at 25℃±2℃ to 2.2V, and record the cell capacity Q3. The capacity retention rate = Q3 / Q2*100%.
[0148] (5) K value test Place the lithium-ion secondary battery at 25℃±2℃ for 4h, discharge at 0.5C to 2.2V, charge at 0.5C to 3.65V, place at 45℃±2℃ for 48h, record the voltage V1, then place at 25±2℃ for 72h, record the voltage V2, K value = (V1-V2) / 72, in mV / h.
[0149] The specific results are recorded in Table 2.
[0150] Table 2 It can be seen from Table 2 that the thermal shrinkage rate of the diaphragm in the battery of the embodiment is low, the 130°C furnace temperature test results of the battery all pass, the 150°C furnace temperature test results are good, the cycle capacity retention rate is high, the 10C rate discharge capacity retention rate is high, and the K value remains basically unchanged, indicating that the battery of the present invention, through the cooperation of the diaphragm and the electrolyte, simultaneously controls the diameter of the pores in the porous structure, the number of pores with a diameter ≥0.5μm, and the coverage rate of pores with a diameter ≥0.5μm on the surface of the ceramic layer, thereby improving the fast charging cycle performance and rate performance of the battery without affecting the safety performance of the battery.
[0151] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.
Claims
1. A battery, It is characterized in that The battery comprises a positive electrode sheet, a negative electrode sheet, an electrolyte and a separator located between the positive electrode sheet and the negative electrode sheet, the separator comprises a substrate and a ceramic layer located on one or both sides of the substrate, the ceramic layer comprises inorganic particles, the ceramic layer is a porous structure, the porous structure comprises pores with a diameter of ≥0.5 μm, the number of pores with a diameter of ≥0.5 μm is 10-800 within a range of 100 μm×100 μm arbitrarily selected on the surface of the ceramic layer, and the coverage rate A1 of pores with a diameter of ≥0.5 μm on the surface of the ceramic layer is 10%-50%; The electrolyte includes an organic solvent, and the organic solvent includes at least two of dimethyl carbonate, ethyl methyl carbonate, propylene carbonate, ethylene carbonate, diethyl carbonate, propyl propionate, ethyl propionate and ethyl acetate.
2. The battery according to claim 1, in, The number of holes with a diameter of ≥0.5 μm in an arbitrarily selected area of 100 μm×100 μm on the surface of the ceramic layer is 50-500; and / or, the coverage rate A1 of the pores with a diameter ≥ 0.5 μm on the surface of the ceramic layer is 15%-45%; And / or, the inorganic particles include one or more of aluminum oxide, boehmite, magnesium oxide, magnesium hydroxide, barium sulfate, barium titanate, zinc oxide, calcium oxide, silicon dioxide, silicon carbide, and boron nitride.
3. The battery according to claim 1, in, The organic solvent includes a first organic solvent and a second organic solvent, the first organic solvent includes one or more of dimethyl carbonate, ethyl methyl carbonate, diethyl carbonate, propyl propionate, ethyl propionate and ethyl acetate, and the second organic solvent includes propylene carbonate and / or ethylene carbonate; the weight ratio of the first organic solvent to the second organic solvent is (0.05-20):
1.
4. The battery according to claim 3, in, The weight ratio of the first organic solvent to the second organic solvent is (0.1-10):
1.
5. The battery according to claim 3, in, Based on the total weight of the electrolyte, the weight content of the organic solvent is 70%-86%.
6. The battery according to claim 5, in, Based on the total weight of the electrolyte, the weight content of the organic solvent is 75%-81%.
7. The battery according to any one of claims 1 to 3, in, The diaphragm satisfies the following relationship: 1<D1 / D2<20, wherein D1 is the average diameter of pores in the ceramic layer with a diameter ≥0.5 μm, in μm; and D2 is the average particle size of the inorganic particles, in μm.
8. The battery according to claim 7, wherein 2≤D1 / D2≤15; and / or, D1 is 0.5 μm-10 μm; And / or, D2 is 0.1 μm-3 μm.
9. The battery according to claim 8, in, D1 is 1μm-8μm; And / or, D2 is 0.5 μm-2 μm.
10. The battery according to any one of claims 1 to 3, in, In a 100μm×100μm range selected arbitrarily on the surface of the ceramic layer, the diameter of the largest hole among the holes with a diameter ≥0.5μm is D5, in μm, and the diameter of the smallest hole among the holes with a diameter ≥0.5μm is D6, in μm. The diaphragm satisfies the following relationship: D5≤4×D6.
11. The battery according to any one of claims 1 to 3, in, The coverage rate of the ceramic layer on the surface of the substrate is 55%-100%; And / or, based on the total volume of the pores in the ceramic layer, the volume of the pores with a diameter of ≥0.5 μm accounts for 20%-80%.
12. The battery according to claim 11, in, The coverage rate of the ceramic layer on the surface of the substrate is 60%-90%; And / or, based on the total volume of the pores in the ceramic layer, the volume of the pores with a diameter of ≥0.5 μm accounts for 30%-60%.
13. The battery according to any one of claims 1 to 3, in, The thickness H1 of the ceramic layer is 1 μm-5 μm; And / or, the porosity K1 of the ceramic layer is 30%-80%; And / or, the surface density of the ceramic layer is 1g / m 2 -8g / m 2 .
14. The battery according to claim 13, in, The thickness H1 of the ceramic layer is 1.5 μm-4 μm; And / or, the porosity K1 of the ceramic layer is 40%-70%; And / or, the surface density of the ceramic layer is 1.5 g / m 2 -6g / m 2 .
15. The battery according to claim 1, in, The organic solvent includes ethyl methyl carbonate, ethyl acetate and propylene carbonate.
16. The battery according to claim 15, in, The weight ratio of ethyl methyl carbonate, ethyl acetate and propylene carbonate in the organic solvent is (10%-70%):(10%-70%):(15%-40%).
17. The battery according to claim 15 or 16, in, The electrolyte further includes LiFSI and optionally an additive, wherein the additive includes one or more of fluoroethylene carbonate, 1,3-propane sultone, vinylene carbonate, lithium difluorophosphate, lithium bisoxalatoborate, lithium difluorooxalatoborate, lithium difluorooxalatophosphate, lithium tetrafluoroborate, and lithium tetrafluorooxalatophosphate.
18. The battery according to claim 17, in, Based on the total weight of the electrolyte, the weight content of LiFSI is 2%-20%; And / or, based on the total weight of the electrolyte, the weight content of the additive is 0%-10%.
19. The battery according to claim 18, in, Based on the total weight of the electrolyte, the weight content of LiFSI is 3%-9%; And / or, based on the total weight of the electrolyte, the weight content of the additive is 1%-8%.
Citation Information
Patent Citations
Membrane for an electrochemical device, electrochemical device comprising the membrane, and method of manufacturing an
CN114868301A
PVDF (Polyvinylidene Fluoride) coated diaphragm as well as preparation method and application thereof
CN115101894A
Cited By
Battery
CN119153895A
A battery
CN119153895B
